The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1247/csf.12.311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on murine megakaryocytopoiesis in a liquid culture system.

Abstract: ABSTRACT. To examine the influence of insulin on megakaryocytopoiesis, we tested its effect on murine bone marrow cultures in a liquid culture system. In the presence of pokeweed mitogen-stimulated spleen cell conditioned medium in culture, insulin markedly enhanced megakaryocyte colony formation and increased the number and size of free megakaryocytes seen after 7 days. Many of the cells in cultures with insulin, however, were classified as immature, since they had a basophillic cytoplasm, a low cytoplasmic/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 5 publications
(1 reference statement)
2
19
0
Order By: Relevance
“…In contrast to the ganglioside fraction, as shown in a previous study (21), insulin potentiated the increase in the number of megakaryocytes in immature state in vitro. In order to examine the interaction of insulin with the ganglioside fraction on murine megakaryocytopoiesis, both substances were applied to the liquid culture system.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…In contrast to the ganglioside fraction, as shown in a previous study (21), insulin potentiated the increase in the number of megakaryocytes in immature state in vitro. In order to examine the interaction of insulin with the ganglioside fraction on murine megakaryocytopoiesis, both substances were applied to the liquid culture system.…”
Section: Resultssupporting
confidence: 46%
“…They suggested that 11-3 can support both megakaryocytic proliferation and maturation in vitro. In the present liquid culture system, more free megakaryocytes were produced than the cells in colonies, and the free mature cells which were stained intensely for acetylcholinesterase could be clearly distinguished from the free immature cells which were stained less intensely (21). The significant potentiation of the increase in the number of immature and mature megakaryocytes by the total ganglioside fraction suggests that the gangliosides play roles in both early and late megakaryocytopoiesis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Another postulated mechanism from a study in mice demonstrated that insulin causes megakaryocytes to produce larger platelets (29). Alternatively, increased platelet size may reflect the presence of high platelet turnover and younger platelets (30).…”
Section: Discussionmentioning
confidence: 99%
“…In a study group of 22 patients with DM, MPV values were higher, but with the decrease in blood glucose, there was a significant decrease in MPV values [9]. It is suggested that insulin potentates murine megakaryocytopoiesis in vitro, in a study; therefore, due to the increased insulin in insulin resistant cases big platelets may be observed [16]. In another study, it is claimed that increased aggregation and multiplication functions occur in diabetic patients' megakaryocyte stem-cells.…”
Section: Discussionmentioning
confidence: 99%